Biophysical Mechanism of the Protective Effect of Blue Honeysuckle (Lonicera caerulea L. var. kamtschatica Sevast.) Polyphenols Extracts Against Lipid Peroxidation of Erythrocyte and Lipid Membranes - Bonarska-Kujawa, D. (Springer US, 2014)
The aim of the present research was to determine the effect of blue honeysuckle fruit and leaf extracts components on the physical properties of erythrocyte and lipid membranes and assess their antioxidant properties. The HPLC analysis showed that the extracts are rich in polyphenol anthocyanins in fruits and flavonoids in leaves. The results indicate that both extracts have antioxidant activity and protect the red blood cell membrane against oxidation induced by UVC irradiation and AAPH. The extracts do not induce hemolysis and slightly increase osmotic resistance of erythrocytes. The research showed that extracts components are incorporated mainly in the external part of the erythrocyte membrane, inducing the formation of echinocytes. The values of generalized polarization and fluorescence anisotropy indicate that the extracts polyphenols alter the packing arrangement of the hydrophilic part of the erythrocyte and lipid membranes, without changing the fluidity of the hydrophobic part. The DSC results also show that the extract components do not change the main phase transition temperature of DPPC membrane. Studies of electric parameters of membranes modified by the extracts showed that they slightly stabilize lipid membranes and do not reduce their specific resistance or capacity. Examination of IR spectra indicates small changes in the degree of hydration in the hydrophilic region of liposomes under the action of the extracts. The location of polyphenolic compounds in the hydrophilic part of the membrane seems to constitute a protective shield of the cell against other substances, the reactive forms of oxygen in particular.